The unusual case of babesiosis causing disseminated intravascular coagulation with hemophagocytic lymphohistiocytosis. Issue 9 (30th August 2021) - Goodman, Alexandra; Bilal, Musa; Amarnath, Shivantha; Gentile, Teresa; Shepherd, Zachary
Abstract: Babesiosis is increasing in the elderly due to an age‐related decline in immunity. Prompt diagnosis with blood smear and PCR prevent life‐threatening complications, like DIC and HLH. Studies focusing on pathophysiology and risk factors are needed. Abstract : Babesiosis is increasing in the elderly due to an age‐related decline in immunity. Prompt diagnosis with blood smear and PCR prevent life‐threatening complications, like DIC and HLH. Studies focusing on pathophysiology and risk factors are needed.